Sosialisasi Membangun Kesadaran Masyarakat Untuk Menjaga Lingkungan Bebas Sampah - Harlina, Risa; Nainggolan, Rico Hasudungan; Pranata, Fheroansyah Ade; Fadila, Ayu; Kuljanah, Julia Mita; Handayani, Sri; Susanti, Neri; Yulianti, Liza (Jurnal Dehasen Untuk Negeri, 2025)
A clean and healthy environment is an essential factor in creating a good quality of life for the community. Waste problems remain a serious issue, both at local and global levels. The lack of public awareness in maintaining environmental cleanliness is one of the main causes of increasing pollution, which negatively impacts health and the surrounding ecosystem. Waste management continues to be an environmental issue that demands serious attention in various regions. The low level of public awareness in maintaining cleanliness contributes to escalating environmental pollution, affecting both human health and ecological balance. Socialization is one of the effective methods for instilling values of cleanliness and raising public awareness about the importance of caring for the environment. This article highlights the importance of socialization in efforts to build public awareness towards a waste-free environment. Through both direct and indirect socialization activities, it is expected that the community will understand the negative impacts of waste on the environment and be motivated to adopt a clean and healthy lifestyle.